THE IMPACT OF FIRM SIZE ON THE PROFITABILITY OF AGRICULTURAL FIRMS IN THE REPUBLIC OF SERBIA - Tomašević, Stevan M; Jović, Zoran D; Vlaović Begović, Sanja M (Journal of Agricultural Sciences (Belgrade), 2019)
The size of the enterprise is one of the most important determinants of profitability of the enterprise. Some domestic and numerous foreign authors have tried to point out the impact that the size of the enterprise has on profitability. The results of these surveys were contradictory, they showed that larger enterprises are more profitable, some that smaller enterprises are more profitable, and there are also studies that have indicated that the size of the enterprise has no impact on profitability. Precisely these contradictory conclusions led the authors of this paper to investigate the impact of the size of enterprise on profitability. This survey used data from regular financial statements for 121 agricultural enterprises for the period 2014 to 2017. The rate of return on assets (ROA) was used as a measure of the profitability of agricultural enterprises, while the size of each individual enterprise was taken from the official statements of these enterprises according to the Company Classification Act. The results of the research have shown that larger enterprises are more profitable compared to small and medium-sized enterprises, but that this difference in performance is not statistically significant. It is a general conclusion that the size of the enterprise does not have a statistically significant impact on the profitability of the sampled agricultural enterprises.
Keywords: agricultural enterprises; profitability; return on assets (ROA); enterprise size; the Kruskal-Walllis test